Potensi Pembangunan Pembangkit Tenaga Mini Hidro (PLTM) pada Sungai Batang Kenaikan Kabupaten Pasaman Barat - Februarman, Februarman; Hardiyanto, Hendri; Hadie, Muhamad Shubhi Nurul (Jurnal Bangunan, Konstruksi & Desain, 2023)
Rivers that flow from hilly or mountainous areas can be used for various purposes including; sources of drinking water, irrigation, fisheries, power plants, and downstream shipping lanes. West Sumatra Province is mostly a mountainous area and has many rivers flowing east and west from the Barisan hills. This condition allows the development of hydroelectric power plants that utilize the head and discharge of rivers. One potential development of a mini hydro power plant (PLTM)  is in Batang Panggang, which is located  in Paraman Ampalu Village, Gunung Tuleh District, West Pasaman Regency. The potential for developing a PLTM on the Batang Panggang River is based on topographic conditions that allow for adequate head height and river flow that can produce electrical energy. For this reason, it is necessary to study the potential by selecting the planned discharge so that it can produce several power production values. These various power productions can be taken into consideration in relation to development costs and operating patterns agreed with PT. PLN (Persero). In this study, the data used includes daily discharge data from automatic water level record (AWLR) recording over the last 15 years. From the discharge data, a Flow Duration Curve (FDC) can be drawn to determine the relationship between discharge and the probability of its occurrence, and this is used as a basis for selecting generator discharge plans and annual energy production. Based on the topographic conditions of the location, the elevation of the lighthouse weir is planned at an altitude of +200 m above sea level, the calming tank is at an altitude of +197 m and the location of the power house is at an altitude of +150 m, while the length of the carrier channel is 2400 m. From this elevation, the height of the fall, H, is 50 m. Assuming the effective fall height, Heff  is 90%xH, then Heff is obtained as 45 m. By trying the planned discharge used is Q40% to Q80%, from the FDC we get Q40% = 17.97 m3/s, Q50% = 14.99 m3/s, Q60% = 12.98 m3/s, Q70% = 11.17 m3/s, and Q80% =   9.54 m3/s. Based on the fall height and design discharge, the appropriate type of turbine is a French turbine and the generator efficiency is 0.95, then the annual  energy for each Qplan is obtained, namely; W40 = 40413.97 MWh, W50 = 37108.22 MWh, W60 = 34744.17 MWh, W70 = 31296.90 MWh, and W80 = 27606.57 MWh.